The Effect of Calcium Soap Supplementation in Feed on Histology of Native Chicken Meat - Nyoman Pande Aryanti (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2025)
This study aims to examine the effects of adding calcium soap (CA-PFAD) to the diet on the histology of meat from native chickens aged 12 weeks. This research took place for 6 weeks at the Sesetan Farm barn, Faculty of Animal Husbandry, Udayana University, located on Jalan Raya Sesetan, Gang Markisa, Denpasar, Bali. The design used was a Completely Randomised Design (CRD) with four treatments and six replications, so there were 24 experimental units. Each experimental unit used 3 chickens aged 6 weeks with a body weight of 662.85 ± 21.02 g. The four treatments were levels of calcium soap in ratios of 0%, 2%, 4%, and 6% respectively, for treatments A, B, C, and D. Variables observed included: histology of meat. The results of the study showed that the addition of calcium soap had a significant effect (P<0.05) on epimysium, perimysium of Balitbangtan superior village chickens (KUB), and reduced fat levels in endomysium chest muscle connective tissue of KUB chicken. Based on the research results, it can be concluded that the addition of calcium soap in the ration at levels of 2% can increase the thickness of the epimysium and perimysium and reduce the thickness of the endomysium in KUB chickens. Based on the results of this study, it can be recommended to farmers and future researchers that adding 2% calcium soap to the feed can increase the thickness of the epimysium and perimysium of KUB chickens.